2010
DOI: 10.1111/j.1749-4877.2010.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ENSO‐driven precipitation on population irruptions of the Yangtze vole Microtus fortis calamorum in the Dongting Lake region of China

Abstract: The Yangtze vole (Microtus fortis Buechner, 1889) is a small herbivore species that inhabits lake beaches in the Dongting Lake region along the Yangtze River in Southern China. Its population shows strong oscillations during the wet season due to summer precipitation-induced immigration away from the lake into adjacent rice fields. The effect of El Niño-Southern Oscillation-driven precipitation on population abundance and growth of the vole species is not fully understood. We undertook an analysis of the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…also southern China (35). Heavy rain also caused high mortality of the Yangtze voles (Microtus fortis) living in close proximity to Dongting Lake's beaches (36,37), and its population size was found to be negatively correlated with water levels of Dongting Lake (38). Precipitation thus tends to have negative effects on rodent plague hosts in southern China.…”
Section: Discussionmentioning
confidence: 99%
“…also southern China (35). Heavy rain also caused high mortality of the Yangtze voles (Microtus fortis) living in close proximity to Dongting Lake's beaches (36,37), and its population size was found to be negatively correlated with water levels of Dongting Lake (38). Precipitation thus tends to have negative effects on rodent plague hosts in southern China.…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak of rodent populations 15 months after cyclone Nargis is consistent with the time it would take for rodent populations in agricultural landscapes to build from a low base after a major weather event. For example, Singleton reported a 12–15 month build‐up of house mouse, Mus domesticus , populations, which reached densities greater than 1000 ha −1 in wheat fields in southeastern Australia, and Zhang et al reported that massive outbreaks of the Yangtze vole, Microtis fortis , in rice fields in southeastern China at Dongting Lake were related to low rainfall the previous year and high rainfall during the year of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evaluation of the small mammal communities was divided into 4 periods, based on the stage of water storage: (i) before construction in the 1990s (1992-1994, and fragmentary surveys in 1997-1999); (ii) the first partial filling period (2003)(2004)(2005)(2006); (iii) the second partial filling period (2007)(2008); and (iv) during experimental water storage to a final water level of 175 m (2009)(2010)(2011)(2012). Data from each period were pooled for the analysis of community structure, because of the low number of captured individuals of some species, to overcome the issue of occasional surveys in each single investigation, and to smooth the influence of strong oscillations of M. fortis (Zhang et al 2010b). Only 1 sampling site was continuously surveyed in the 1990s (the beach outside of Matang Polder); hence, fragmentary surveys from other locations were pooled with this dataset to provide an overview of the situation before the TGP, allowing overall trap success to be calculated for all nights during which traps were set in each period.…”
Section: Discussionmentioning
confidence: 99%